2013
DOI: 10.1176/appi.ps.201200484
|View full text |Cite
|
Sign up to set email alerts
|

Mental Illness and Domestic Homicide: A Population-Based Descriptive Study

Abstract: A significant minority of adult domestic homicide perpetrators had symptoms of mental illness at the time of the homicide. Most perpetrators, including those with mental illnesses, were not in contact with mental health services in the year before the offense. Risk reduction could be achieved through initiatives that encourage individuals with mental health problems to access mental health services and that develop closer interagency working, including between mental health services, police, social services, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
61
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 25 publications
13
61
0
5
Order By: Relevance
“…Furthermore, when a woman commits an intrafamilial murderespecially if the victim is a childthe crime is generally associated with psychotic motivation, which normally excludes psychopathic motivations. This is consistent with research demonstrating that intrafamilial homicides have a higher association with psychosis than extrafamilial homicides (Oram, Flynn, Shaw, Appleby, & Howard, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, when a woman commits an intrafamilial murderespecially if the victim is a childthe crime is generally associated with psychotic motivation, which normally excludes psychopathic motivations. This is consistent with research demonstrating that intrafamilial homicides have a higher association with psychosis than extrafamilial homicides (Oram, Flynn, Shaw, Appleby, & Howard, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, previous research has focused on direct relationships between homicide method and a mental illness per se (Minero et al, ) and do not account for circumstance surrounding the offence and type of victim. This pattern is consistent with previous research on adult family homicide reporting schizophrenia as the most prevalent diagnosis (Oram et al, ). Thus, our findings suggest the previously reported association between schizophrenia and sharp instruments may differ in cases where the victim is female, over 55 years, and the homicide is preceded by a domestic dispute.…”
Section: Discussionsupporting
confidence: 92%
“…This led Häkkänen () to propose that future research should focus on samples of homicide offenders with mental illness to establish whether specific offence characteristics might be linked to a particular psychiatric disorder. Findings have shown that homicide offenders with and without a mental illness differ from each other in their offence, demographic, and background characteristics (Häkkänen, ; Oram, Flynn, Shaw, Appleby, & Howard, ). For example, offenders with mental illness are less likely to have strangers as victims (Shaw et al, ), more likely to be older (Martone et al, ), and have more problematic backgrounds (Häkkänen & Laajasalo, 2006) compared with offenders without a mental illness.…”
Section: Introductionmentioning
confidence: 99%
“…Women, however, are more likely to experience sexual violence, severe physical violence or be murdered by a partner than men (Chermack et al, ; World Health Organization, ). Demographic (younger age and low socio‐economic status), distal (negative childhood experiences), proximal (substance use, psychological problems and anger expression) and cultural (sexist attitudes and support of gender‐specific roles) have all been associated with intimate partner violence perpetration (Dutton, ; Cunradi et al, ; Stith et al, ; Gil‐González et al, ; Oram et al, ; Ten Have et al, ). Leonard (: 422) wrote:
Excessive alcohol consumption is one of the most controversial risk factors.
…”
Section: Introductionmentioning
confidence: 99%